'Boswellized From Mere Persons to Personages': Arthur Stringer, Mary Pickford, and the Trouble with Celebrity Profile(r)s. Issue 2 (3rd April 2019) - Lee, Katja
ABSTRACT: In 1918, MacLean's magazine published an extensive profile of Canadian-born silent screen superstar, Mary Pickford. Spanning three issues and inclusive of twenty-seven photographs, 'Our Mary' was one of the most substantial profiles of a public figure ever published by the magazine, and it was written by no less a personality than the eminently respected, popular Canadian writer Arthur Stringer. Yet Stringer does not seem entirely at ease with celebrity journalism, and 'Our Mary' not only gives us some insight into the practices of celebrity profiling as a particular species of celebrity life writing, but also a language for its critique. From Stringer's conflicted engagement with the genre emerges a portrait of the troubled and troubling celebrity profiler: an individual not only tasked with serving many masters and having to negotiate what might be perceived as loathsome generic conventions, but having to adopt a particular kind of persona in order to do so. Thus, while Stringer explicitly and repeatedly seeks to separate himself and his work from that genre of journalism that will 'Boswelliz[e celebrities] from mere persons to personages', 'Our Mary' also tacitly acknowledges the role he must play in this game.